(untitled) (Global Journal of Management and Business Research, 2023)
Green investments play an important role in achieving the sustainable development goals and creating an environmentally friendly structure of the economy as a whole At the same time at the present stage there is a significant deficit of green investment which is largely a consequence of the imbalance between short-term financial and long-term environmental interests Among the main reasons for the lack of green investments attractiveness is their increased riskiness from the point of view of existing financial markets The existing system for assessing investments within the framework of the risk-return matrix does not fully take into account a number of social and environmental effects that do not have a direct monetary value and do not contribute to increasing market returns Based on the analysis of the category of green investments itself as well as the risks associated with it the article proposes a comprehensive approach to managing investment risks based on their structurally functional classification and inclusion of potential effects from reducing environmental risks in the analysis